Intercellular propagation of RIPK1/RIPK3 amyloid fibrils - Yeyang Ma; Qiuyuan Zhang; Dekang Li; Kun Zhao; Zefei Li; Yuan Liu; Chu Wang; Bo Sun; Dan Li; Junying Yuan; Cong Liu (Proceedings of the National Academy of Sciences, 2025)
The canonical necrosome formed by receptor-interacting protein kinase 1 (RIPK1) and RIPK3 is a functional amyloid fibril structure critical to intracellularly drive necroptosis. Since necroptosis leads to the release of intracellular content, the fate of RIPK1/RIPK3 fibrils after necroptotic cell death has not been investigated. Here, we tracked RIPK1 and RIPK3 coassemblies and found that these fibrillar aggregates could be released into the culture medium after the membrane rupture in necroptotic cells. Interestingly, these RIPK1/RIPK3 fibrils were capable of infiltrating recipient cells and acting as seeds for the nucleation and formation of the endogenous necrosome. Cryo electron microscopy structural analysis unveiled a distinctive S-shaped conformation common to RHIM fibrils of RIPK1 and RIPK3, which can facilitate the cross-seeding of RIPK3 by RIPK1 or RIPK1/RIPK3 fibrils. Our findings suggest the ability of functional RIPK1/RIPK3 amyloid fibrils in intercellular spreading to induce protein conformation change in recipient cells and provide structural insights into the mechanism of RIPK1 and RIPK3 cross-templating to drive necroptosis.